The Conceptual Foundations of the Institutional and Instrumental Support for the Development of a Resilient Economy of Ukraine - Kyzym Mykola O.; Khaustova Viktoriia Ye.; Yudenko Yevhen V. (Problemi Ekonomiki)
The article is aimed at forming the conceptual foundations of the institutional and instrumental support for the development of a resilient economy in Ukraine. It is proposed to analyze the development of the country’s economy in the context of a component of a super-complex system – society, which is proposed to be considered as a set of such spheres of people’s life: political, social, economic, and environmental. The views of scientists on the content of the concept of resilience of society and its spheres are considered and a cybernetic model of managing the resilience of society in the country is formed. A scheme of interconnection of concepts close to the concept of «resilience» has been developed, and an interpretation of the concept of «resilience of society» has been suggested. Further on, a conceptual model for studying the resilience of society has been proposed. A model of the stages of the life cycle of an event in relation to society in the country has been formed. It is substantiated that the resilience of the economy is a component of the resilience of society and it should be considered from two aspects: as a potential, i. e. a set of available opportunities and means in any sphere of society that can be used in the impact of crises (shocks) of various nature and as a result of the effect of a crisis (shock) in the long and short term on the economic sphere. An operational model for ensuring the resilience of society in the country is suggested. The properties of resilience of society are generalized. It is substantiated that the conception of resilience is the methodological basis for determining the institutional tools for the post-war development of the resilient economy of Ukraine, and in order to ensure the resilience of society, it is necessary to have a management system that would correspond to the intensity of the crisis (shock) and the appropriate response to this. In case of a weak crisis (shock) affecting certain areas of society, the best management system to counter it is determined to be anticipative management based on weak signals. The essential difference between anticipative, adaptive and anti-crisis systems of society management has been studied and a scheme of the sequence of anti-crisis transformation of society has been formed. The institutional and instrumental support of the resilience of society is determined. It is proved that studies of any processes and phenomena are based on putting forward and proving / refuting certain hypotheses. Several descriptive, descriptive-explanatory and explanatory hypotheses in the field of societal resilience studies have been formed. The presented hypotheses form the basis of the conception of institutional and instrumental support for the development of a resilient economy in Ukraine.